Organ preservation: current limitations and optimization approaches - Ran, Qiulin; Zhang, Jiayi; Zhong, Jisheng; Lin, Ji; Zhang, Shuai; Li, Guang; You, Bin (Frontiers in Medicine, 2025)
Despite the annual rise in patients with end-stage diseases necessitating organ transplantation, the scarcity of high-quality grafts constrains the further development of transplantation. The primary causes of the graft shortage are the scarcity of standard criteria donors, unsatisfactory organ preservation strategies, and mismatching issues. Organ preservation strategies are intimately related to pre-transplant graft viability and the incidence of adverse clinical outcomes. Static cold storage (SCS) is the current standard practice of organ preservation, characterized by its cost-effectiveness, ease of transport, and excellent clinical outcomes. However, cold-induced injury during static cold preservation, toxicity of organ preservation solution components, and post-transplantation reperfusion injury could further exacerbate graft damage. Long-term ex vivo dynamic machine perfusion (MP) preserves grafts in a near-physiological condition, evaluates graft viability, and cures damage to grafts, hence enhancing the usage and survival rates of marginal organs. With the increased use of extended criteria donors (ECD) and advancements in machine perfusion technology, static cold storage is being gradually replaced by machine perfusion. This review encapsulates the latest developments in cryopreservation, subzero non-freezing storage, static cold storage, and machine perfusion. The emphasis is on the injury mechanisms linked to static cold storage and optimization strategies, which may serve as references for the optimization of machine perfusion techniques.